Effect of carbohydrate supplementation on the physiological and perceptual responses to prolonged tennis match play - Gomes, R. V.; Moreira, A.; Coutts, A. J.; Capitani, C. D.; Aoki, M. S. (The Journal of Strength and Conditioning Research, 2014)
Carbohydrate supplementation is a popular nutritional practice used in tennis to enhance physical capacities, motor-skill performance, and delay fatigue. However, the effects of carbohydrate supplementation on physiological and perceptual responses during tennis match play are not established. This double blind, randomized, placebo (PLA)-controlled crossover study was designed to determine the influence of carbohydrate supplementation (0.5 g/kg/h) on glycemia, salivary hormones (cortisol and testosterone) concentration, salivary immunoglobulin A (IgA) concentration, and rating of perceived exertion (RPE) during 3 hours of tennis match play in 12 well-trained tennis players. The only significant difference between the 2 conditions was a lower salivary cortisol concentration postmatch in the carbohydrate trial (p < 0.05); however, there was a trend for higher glucose concentration (p = 0.06) and lower session-RPE (p = 0.08) after tennis match play in the carbohydrate condition, which may have some practical implications. There was no change in salivary testosterone, salivary IgA, and RPE responses during tennis match play between conditions (p > 0.05). These data indicate that carbohydrate ingestion during 3 hours of competitive tennis match play helps to maintain glycemia and attenuates the increase in salivary cortisol concentration compared with PLA.